Efforts to improve problem solving skills and critical thinking skills through problem-based integrated Computer Assisted Instruction (CAI) in Vocational Education - Wulansari, Rizky Ema; Nabawi, Rahmat Azis (Jurnal Pendidikan Teknologi Kejuruan, 2021)
Based on research conducted by PISA, the ability to solve problems and think critically of Indonesian students is still below the average score set by PISA. Problem based learning is one of the learning models recommended by the Ministry of Education and Culture to be applied in improving these abilities. However, the lack of problem-based learning that has been applied so far is the lack of use of media that can be used as support in learning activities, resulting in inconsistencies in the impact of problem-based learning in improving student skills. The importance of these skills for students to have in this era of the industrial revolution 4.0, makes educators have to be more creative and innovative in implementing learning. Therefore, this study aims at seeing efforts to improve problem solving skills and critical thinking skills through problem based integrated computer assisted instruction (CAI). This study used a quasi-experimental pre-test and post-test control group design. The population in this study were undergraduate students of Mechanical Engineering Education, Padang State University. The instrument used in this research is a questionnaire which is used to see students' problem solving and critical thinking skills. The data analysis technique in this study is in accordance with the research hypothesis, where research hypotheses 1 and 2 use independent sample t-test and research hypothesis 3 uses MANCOVA. The research covered by his study is in line with higher education's continuing search for effective SCL approaches